2012
DOI: 10.1111/j.1476-5829.2012.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Receptor tyrosine kinase inhibitors: molecularly targeted drugs for veterinary cancer therapy

Abstract: Tyrosine kinases (TKs) are key mediators of signalling pathways in cells. Located at the surface of the cell, within the cytoplasm or in the nucleous, TKs have been showed to be involved in regulation of normal cellular processes and also play an important role in the development, progression and spread of several types of cancer. Seventy percent of TK's are Receptor Tyrosine Kinases and these have become key targets for cancer therapy. This short synopsis is intended to give the reader an introduction to this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 69 publications
1
31
0
2
Order By: Relevance
“…While tyrosine kinase inhibitors (TKIs) are routinely employed in human oncology with success, their use in veterinary medicine is limited. Two small molecule tyrosine kinase inhibitors, toceranib (TOC) phosphate (Palladia®; Zoetis, Madison, NJ) and masitinib (Masivet®, Kinavet®; AB Science, Paris, France) have been approved by the FDA for use in veterinary medicine for the treatment of recurrent, non-resectable intermediate and high grade canine cutaneous mast cell tumors (MCTs) [1]. The success of targeted therapies in both human and veterinary oncology, however, is largely tempered by the inevitable development of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…While tyrosine kinase inhibitors (TKIs) are routinely employed in human oncology with success, their use in veterinary medicine is limited. Two small molecule tyrosine kinase inhibitors, toceranib (TOC) phosphate (Palladia®; Zoetis, Madison, NJ) and masitinib (Masivet®, Kinavet®; AB Science, Paris, France) have been approved by the FDA for use in veterinary medicine for the treatment of recurrent, non-resectable intermediate and high grade canine cutaneous mast cell tumors (MCTs) [1]. The success of targeted therapies in both human and veterinary oncology, however, is largely tempered by the inevitable development of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This therapy consists in a continuous administration of compounds inhibiting angiogenesis, and has immunomodulatory effects on the neoplasm inducing hypoxia, nutrient deprivation and tumour growth arrest (Lana and others 2007, London and others 2012, Mitchell and others 2012). Drugs used include, alkylanting agent (cyclophosphamide, chlorambucil, melfalan), nonsteroidal anti-inflammatory drugs (piroxicam, meloxicam, coxib) and/or tyrosine kinase inhibitor (TKI) such as TP (Lana and others 2007, Mutsaers 2009, Bavcar and Argyle 2012). …”
Section: Discussionmentioning
confidence: 99%
“…TP is an inhibitor of some tyrosine kinase receptors, such as vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptor, stem cell factor receptor (Kit), colony stimulating factor-1 receptor and FMS-like tyrosine kinase 3 (Flt-3 C) (Bavcar and Argyle 2012). A few cases of human angiosarcomas have reported durable disease stabilisation with TKIs due to an unknown mechanism or inhibition of VEGFR-2 receptor (Kiesel and others 2009, Yoo and others 2009, Tokuyama and others 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Masitinib targets PDGFR‐α, PDGFR‐β, KIT, Lyn, and to a lesser degree, the FGFR3 and FAK pathways as well as VEGFR‐2, and is conditionally approved by the United States Food and Drug Administration and the European Medicines Agency for use against canine mast cell tumours. Studies evaluating its clinical efficacy against sarcomas are lacking, although one study demonstrated antiproliferative activity against canine oral fibrosarcoma in vitro …”
Section: Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…This is illustrated by a growing number of clinical and preclinical studies evaluating safety and efficacy of these TKIs as single therapy or in combination with traditional cytotoxic chemotherapeutic agents and/or cyclooxygenase (COX) inhibitors. 35,178,[184][185][186][187][188] Proposed mechanisms supporting their use in combination with other agents include chemosensitization as well as immunomodulation through suppression of regulatory T cells and restoration of T cell-mediated immune responses. 108,189 Toceranib is a multitargeted TKI targeting several RTKs, including VEGFR, PDGFR, KIT, CSF1R, and FLT3 and was developed as an orally bioavailable anti-angiogenic drug.…”
Section: Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 99%